PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE INSTANT ASSESSMENT UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN HIDROKARBON DI KELAS X SMA YLPI PEKANBARU (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The application of active learning strategy instant assessment type to improve the students achievement on the subject of hydrocarbon in class X SMA YLPI Pekanbaru has been done. The research is a experiment research with pretest-posttest design. The population consisted of four classes grade. The sample were two classes, where class X 2 as an experimental class and the class X 4 as an control class. They were selected after normality and homogeneity test. Experimental class is a class that was applied to active learning strategy instant assessment type while the control class was not. Data analysis technique used is the t-test and gain normalized test. Based on data analysis obtained tcount > ttable (5,74>1,66), means that application of active learning strategy instant assessment type can improve student learning achievement on the topic of hydrocarbon in class X Senior High School (SMA) YLPI Pekanbaru. The category improvement of student achievement at experiment class was high category with N-gain normalized is 0,78. Meanwhile, the category improvement of student achievement in control class was medium category with N-gain normalized is 0,69.Keywords : Learning Achievement, Active Learning Strategy Instant Assessment Type, Hydrocarbon